Biased recipients encounter biased sources: Effect of ethical (dis‐)agreement between recipient and author on evaluating scientific claims. Issue 6 (30th April 2019) - Scharrer, Lisa; Stadtler, Marc; Bromme, Rainer
Summary: Scientific claims that are connected to ethical concerns are frequently brought forward by communicators who are not ethically neutral. This study investigated how far recipients' evaluation of such claims is guided by vigilance toward a potential ethical source bias rather than their own ethical bias. One hundred ten individuals opposed to capital punishment read a topic‐related text by an ethically positioned source. A scientific claim in the text either supported or did not support the recipient's ethical stance; in addition, the source either shared or opposed their stance. Results showed that recipients are guided to some extent by their own ethically motivated reasoning: They agree more consistently with sources sharing their ethical stance and consider these sources to be more credible. Recipients appear to be principally aware that a source's ethical stance may bias its scientific message, but this vigilance seems to depend on their own ethical disagreement with the source.